Liquid level control: Simplicity and complexity. (February 2020) - Luyben, William L.
Abstract: From a superficial perspective, the control of liquid level in a vessel is a "non-problem." Well-known process control heuristics advise using a proportional-only controller with a gain K c = 2. However many plant operators are uncomfortable with the resulting "offset" ("steady-state error" or "droop") between the process variable and the controller setpoint that is inherent in a proportional controller because of the lack of integral action to drive the error to zero. Therefore level controllers with proportional-integral (PI) action are often found in process units. The purpose of this paper is to illustrate that PI control does not provide effective attenuation of flow disturbances and that it actually amplifies them. We also show that PI level controllers can give confusing tuning results. In most closedloop systems, increasing controller gain makes the system more oscillatory (smaller closedloop damping coefficient). When PI controllers are used to control liquid level, the exact opposite occurs (increasing controller gain makes the system less oscillatory).